# SOLUTION: Can someone please check my work? Thank you Question: Multiply x – 2 by -5x2 – 3x – 4 Answer: (x – 2)(-5x^2 – 3x – 4 ) = 5x^3 - 3x^2 - 4x + 10x^2 + 6x + 8 = 5x^3 -

Algebra ->  Algebra  -> Polynomials-and-rational-expressions -> SOLUTION: Can someone please check my work? Thank you Question: Multiply x – 2 by -5x2 – 3x – 4 Answer: (x – 2)(-5x^2 – 3x – 4 ) = 5x^3 - 3x^2 - 4x + 10x^2 + 6x + 8 = 5x^3 -      Log On

 Ad: Algebra Solved!™: algebra software solves algebra homework problems with step-by-step help! Ad: Algebrator™ solves your algebra problems and provides step-by-step explanations!

 Algebra: Polynomials, rational expressions and equations Solvers Lessons Answers archive Quiz In Depth

 Question 601713: Can someone please check my work? Thank you Question: Multiply x – 2 by -5x2 – 3x – 4 Answer: (x – 2)(-5x^2 – 3x – 4 ) = 5x^3 - 3x^2 - 4x + 10x^2 + 6x + 8 = 5x^3 - 3x^2 + 10x^2 - 4x + 6x + 8 = 5x^3 + 8x^2 + 2x + 8 Question: Subtract. (4n6 – 7n5 + 5) – (9n6 – n5 + 8) Answer: 4n^6 - 7n^5 + 5 - 9n^6 + n^5 - 8 = (4 -9)n^6 + (7 - 1)n^5 - 3 =(-5) n^6 + (-6)n^5 - 3 = -5n^6 - 6n^5 -3 Answer by Alan3354(30955)   (Show Source): You can put this solution on YOUR website!Question: Multiply x – 2 by -5x2 – 3x – 4 Answer: (x – 2)(-5x^2 – 3x – 4 ) = 5x^3 - 3x^2 - 4x + 10x^2 + 6x + 8 = 5x^3 - 3x^2 + 10x^2 - 4x + 6x + 8 = 5x^3 + 8x^2 + 2x + 8 -------- It's -5x^3, and -3x^3+10x^3 = 7x^2 = -5x^3 + 7x^2 + 2x + 8 ================================ Question: Subtract. (4n6 – 7n5 + 5) – (9n6 – n5 + 8) Answer: 4n^6 - 7n^5 + 5 - 9n^6 + n^5 - 8 = (4 -9)n^6 + (7 - 1)n^5 - 3 =(-5) n^6 + (-6)n^5 - 3 = -5n^6 - 6n^5 -3 Looks good.